Comparative proteomic study for profiling differentially expressed proteins between Chinese left‐ and right‐sided colon cancers. Issue 1 (17th November 2012) - Shen, Hong; Huang, Jinlin; Pei, Haiping; Zeng, Shan; Tao, Yiming; Shen, Liangfang; Zeng, Liang; Zhu, Hong
<x xml:space="preserve">Abstract</x> The aim of the present study is to profile differentially expressed protein markers between left‐sided colon cancer (LSCC) and right‐sided colon cancer (RSCC). Fresh tumor tissue samples from LSCC (n = 7) and RSCC (n = 7) groups were analyzed by two‐dimensional electrophoresis coupled with MALDI‐TOF‐MS, followed by Western blotting. In 50 paraffin embedded samples from each group, levels of four differentially expressed proteins (identified by proteomics analysis) were measured by tissue microarray with immunohistochemistry staining to compare the different protein markers between LSCC and RSCC. Sixteen proteins were found to be differentially expressed between LSCC and RSCC. Ten proteins including HSP‐60 and PDIA1 were identified to be highly expressed in LSCC (P < 0.01 or P < 0.05), while the expression of six proteins including EEF1D and HSP‐27 were higher in RSCC (P < 0.01 or P < 0.05). Virtually all of the indentified proteins were involved in cellular energy metabolism, protein folding/unfolding, and/or oxidative stress. Human colon tumors at various locations have different proteomic biomarkers. Differentially expressed proteins associated with energy metabolism, protein folding/unfolding and oxidative stress contribute to different tumorigenesis, tumor progression, and prognosis between left‐ and right‐sided colon cancer. (Cancer Sci 2013; 104: 141–135)